2015
DOI: 10.17814/mechanik.2015.2.98
|View full text |Cite
|
Sign up to set email alerts
|

The application of the HIP device produced by AIP company for synthesis of composite materials

Abstract: Streszczenie: W artykule przedstawiono technikę wytwarzania materiałów metalowoceramicznych przy wykorzystaniu obróbki cieplno-ciśnieniowej (HIP). Badania rozpoczęto od określenia parametrów fizykochemicznych jedenastu, zaproponowanych przez technologów firmy GONAR BIS sp. z o.o., kompozycji proszków opartych na bazie węglika wolframu i kobaltu. Stosując technikę mikrofluorescencji rentgenowskiej określono ich skład chemiczny. Wykorzystując różne techniki badawcze określono skład ziarnowy. Otrzymane wyniki uła… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Knowing the dimensions of the cylinder, its weight and density of Ti6Al4V alloy (4.42 g/cm 3 ) it was possible to calculate bulk density of the sample material. The measurements showed that the bulk density of the obtained porous material is 1.32 g/cm 3 . This value allowed to calculate the porosity which was found to be 70%.…”
Section: Fig 2 Measurement Results For the Nacl Crystal Size Applied ...mentioning
confidence: 95%
See 1 more Smart Citation
“…Knowing the dimensions of the cylinder, its weight and density of Ti6Al4V alloy (4.42 g/cm 3 ) it was possible to calculate bulk density of the sample material. The measurements showed that the bulk density of the obtained porous material is 1.32 g/cm 3 . This value allowed to calculate the porosity which was found to be 70%.…”
Section: Fig 2 Measurement Results For the Nacl Crystal Size Applied ...mentioning
confidence: 95%
“…"capsules" filled with metal powders gives a homogeneous material at high temperature and high pressure, the parameters of which are approximate to roll-formed materials. The HIP process follows a predefined program and remains safe if materials are used that do not form eutectic systems [3]. An example of an 'unsafe' material in this regard is the copper-titanium system with the double system eutectic temperature of 875°C [4].…”
Section: Introductionmentioning
confidence: 99%